The implementation of legal framework for the financing of small businesses by digital platforms – crowdfunding – for more investment and jobs in the WAEMU area - (:unkn) unknown (My University, 2024)
The implementation of legal framework for the financing of small businesses by digital platforms – crowdfunding – is of growing significance in the contemporary globalized, digital and intelligent economy. This model of participatory financing – donations, loans, investment – enables start-up companies and African entrepreneurs to raise funds from a large number of individual investors via dedicated online platforms, thus offering an alternative to traditional methods of financing. The regulatory framework could foster digital trust, with more investment, business creation, and employment opportunities within emerging African companies, especially innovative ones which are not yet established on the market, or have specific financial needs. The ultimate aim is to promote and support the growth of small businesses, which are often major drivers of local and regional employment.
Keywords: African Research